Developing Short-Story Writing Materials Based on Strategy-Based Instruction (SBI) for Indonesian Language Education Students - Antonius Totok Pryadi; Khairullah Khairullah; Sonya Ade Putri (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The limited availability of teaching materials that integrate systematic techniques for idea and plot development remains a major obstacle for students in achieving the competency standards of the Creative Writing course. This research aims to develop short story writing materials by integrating the Strategy-Based Instruction (SBI) framework. The method employed is Research and Development (R&D) utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The teaching materials were constructed by synergizing cognitive and metacognitive strategy stages, including strategy identification, modeling, guided practice, and independent writing. Research subjects involved expert validators, a course lecturer, and 28 Indonesian Language Education students at Tanjungpura University. Validation results from material, language, and design experts showed very high average scores (3.88–4.00). Practicality tests on both limited and field scales categorized the materials as highly practical (3.46–3.72). Furthermore, pretest and posttest results (sig. 0.001) significantly proved that these materials are effective in improving students' ability to construct the intrinsic elements of short stories structurally. These findings contribute to a more systematic creative writing instructional model through the reinforcement of procedural strategies for novice writers in higher education.